Conversion, shrinkage, water sorption, flexural strength and modulus of re-mineralizing dental composites. Issue 11 (November 2015) - Aljabo, A.; Xia, W.; Liaqat, S.; Khan, M.A.; Knowles, J.C.; Ashley, P.; Young, A.M.
Abstract: Objectives: Cure, volumetric changes and mechanical properties were assessed for new dental composites containing chlorhexidine (CHX) and reactive calcium phosphate-containing (CaP) to reduce recurrent caries. Methods: 20 wt.% of light curable urethane dimethacrylate based liquid was mixed with 80 wt.% glass filler containing 10 wt.% CHX and 0–40 wt.% CaP. Conversion versus depth with 20 or 40 s light exposure was assessed by FTIR. Solidification depth and polymerization shrinkage were determined using ISO 4049 and 17304, respectively. Subsequent volume expansion and biaxial flexural strength and modulus change upon water immersion were determined over 4 weeks. Hydroxyapatite precipitation in simulated body fluid was assessed at 1 week. Results: Conversion decreased linearly with both depth and CaP content. Average solidification depths were 4.5, 3.9, 3.3, 2.9 and 5.0 with 0, 10, 20, and 40% CaP and a commercial composite, Z250, respectively. Conversions at these depths were 53 ± 2% for experimental materials but with Z250 only 32%. With Z250 more than 50% conversion was achieved only below 1.1 mm. Shrinkage was 3% and 2.5% for experimental materials and Z250, respectively. Early water sorption increased linearly, whilst strength and modulus decreased exponentially to final values when plotted versus square root of time. Maximum volumetric expansion increased linearly with CaP rise and balanced shrinkage at 10–20 wt.% CaP. Strength and modulus for Z250 decreased from 191 to 158 MPa and 3.2 to 2.5 GPa. Experimental composites initial strength and modulus decreased linearly from 169 to 139 MPa and 5.8 to 3.8 GPa with increasing CaP. Extrapolated final values decreased from 156 to 84 MPa and 4.1 to 1.7 GPa. All materials containing CaP promoted hydroxyapatite precipitation. Significance: The lower surface of composite restorations should both be solid and have greater than 50% conversion. The results, therefore, suggest the experimental composite may be placed in much thicker layers than Z250 and have reduced unbounded cytotoxic monomer. Experimental materials with 10–20 wt.% additionally have volumetric expansion to compensate shrinkage, antibacterial and re-mineralizing components and competitive mechanical properties.